Evaluation of the Supply Process in Public Hospitals: A Qualitative Study - Demet Kavak; Şafak Çınar; Ugur Ugrak; Fırat Seyhan (Verimlilik Dergisi)
Purpose: The purpose of this qualitative study is to examine the healthcare supply process in public hospitals in a multi-dimensional manner and to reveal the weaknesses and strengths in this process.Method: This qualitative study was conducted among stakeholders with sufficient knowledge and experience about healthcare supply processes in public hospitals. Within this research scope, semi-structured interviews were conducted with 14 participants determined using purposeful and snowball sampling methods. The data was analyzed using the thematic coding method with an inductive interpretive phenomenology approach. Nvivo 2020 software was used during the analysis process.Findings: The current legislation in Türkiye was observed to allow for various supply methods. The open tender method was determined to be the best cost-advantage one in terms of economy of scale. However, it may cause a decrease in material quality. Therefore, well-designed specifications and qualified human resources play an essential role in the supply process.Originality: This study reveals the possible negative effects of a cost-oriented approach in the supply process on quality in public hospitals. Additionally, the necessity of quality human resources in the supply process of healthcare was identified as an important problem. Informal structures were also emphasized among suppliers, which may disrupt the competitive environment.